Application of compressor water injection for the reduction of civil aircraft NOᵪ emissions. - Block Novelo, David Alejandro (Cranfield University, 2018)
Gas turbine Nitrogen Oxide (NOx) emissions are directly proportional to combustion temperature. These contaminants are associated with respiratory diseases and damage to the local water quality and wildlife. Higher demand on civil aviation, coupled to high-pressure ratio (and thus, temperature-ratio) engines, have caused aviation-borne NOᵪ Gas turbine Nitrogen Oxide (NOx) emissions are directly proportional to combustion temperature. These contaminants are associated with respiratory diseases and damage to the local water quality and wildlife. Higher demand on civil aviation, coupled to high-pressure ratio (and thus, temperature-ratio) engines, have caused aviation-borne NOᵪ emissions to double since 1990. This is of concern around airports, at operations below 3,000 ft. where the concentration of air traffic is high and the population faces direct exposure to engine contaminants. This thesis explores the use of atomized water droplets into an engine compressor as a way of intercooling the cycle and in doing so reducing NOᵪ emissions. The use of water injection is proposed to be applied only during take-off and climb up to 3,000 ft. The analysis of water injection is firstly applied to common turbofan architectures (2 and 3-spool), under varied ambient conditions. The gas turbines are simulated by means of an in-house performance simulating tool, Turbomatch. The changes in cycle temperature when water injection is applied, are accounted for by means of a stand-alone analytical compressor model. The platform calculates the thermodynamic exchange between the gas path of the engine and the water droplets in the Lagrangian frame of reference. The engine models are then integrated into an in-house aircraft performance simulating tool, Hermes. Two types of aircraft, narrow and wide-body, are considered for operations with the water injection system. The performance benefits noted in the stand-alone engine section, are evaluated considering the extra system weight for different missions ranging from 500 to 11,000 km. The observed theoretical trends are then confirmed by means of an experiment performed on a stationary gas turbine. The test includes performance monitoring (pressures, temperatures, mass flows), water droplet measurements, and exhaust emissions analysis. The most optimistic case of water injection shows a reduction of NOx emissions greater than 50%, for the period when water is used. This technology, when applied after the fan compressor, is effective at ambient temperatures as low as 5°C and is more promising in 3-spool engines. For the shortest mission considered, equivalent to a journey from London to Paris, the aircraft benefits from a small fuel saving, despite of the extra weight. For longer missions, there is a negligible fuel penalty (0.05%) derived from the extra payload. In all the cases Landing and Take-Off (LTO) emissions are estimated to be reduced by 42-43%. A reduction of NOx emissions of 25% is achieved experimentally when injecting 2% water-to-air ratio. The study concludes that compressor water injection is a feasible solution that can significantly reduce the environmental footprint of aviation emissions to double since 1990. This is of concern around airports, at operations below 3,000 ft. where the concentration of air traffic is high and the population faces direct exposure to engine contaminants. This thesis explores the use of atomized water droplets into an engine compressor as a way of intercooling the cycle and in doing so reducing NOᵪ emissions. The use of water injection is proposed to be applied only during take-off and climb up to 3,000 ft. The analysis of water injection is firstly applied to common turbofan architectures (2 and 3-spool), under varied ambient conditions. The gas turbines are simulated by means of an in-house performance simulating tool, Turbomatch. The changes in cycle temperature when water injection is applied, are accounted for by means of a stand-alone analytical compressor model. The platform calculates the thermodynamic exchange between the gas path of the engine and the water droplets in the Lagrangian frame of reference. The engine models are then integrated into an in-house aircraft performance simulating tool, Hermes. Two types of aircraft, narrow and wide-body, are considered for operations with the water injection system. The performance benefits noted in the stand-alone engine section, are evaluated considering the extra system weight for different missions ranging from 500 to 11,000 km. The observed theoretical trends are then confirmed by means of an experiment performed on a stationary gas turbine. The test includes performance monitoring (pressures, temperatures, mass flows), water droplet measurements, and exhaust emissions analysis. The most optimistic case of water injection shows a reduction of NOᵪ emissions greater than 50%, for the period when water is used. This technology, when applied after the fan compressor, is effective at ambient temperatures as low as 5°C and is more promising in 3-spool engines. For the shortest mission considered, equivalent to a journey from London to Paris, the aircraft benefits from a small fuel saving, despite of the extra weight. For longer missions, there is a negligible fuel penalty (0.05%) derived from the extra payload. In all the cases Landing and Take-Off (LTO) emissions are estimated to be reduced by 42-43%. A reduction of NOx emissions of 25% is achieved experimentally when injecting 2% water-to-air ratio. The study concludes that compressor water injection is a feasible solution that can significantly reduce the environmental footprint of aviation.
Keywords: Engine performance; NOᵪ reduction; aircraft performance; gas turbine; experiment; water injection